2018
DOI: 10.3390/app8040642
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of Stagnation-Point Flow in a Nanofluid over a Stretching/Shrinking Sheet with Second-Order Slip, Soret and Dufour Effects: A Revised Model

Abstract: The mathematical model of the two-dimensional steady stagnation-point flow over a stretching or shrinking sheet of nanofluid in the presence of the Soret and Dufour effects and of second-order slip at the boundary was considered in this paper. The partial differential equations were transformed into the ordinary differential equations by applying a suitable similarity transformation. The numerical results were obtained by using bvp4c codes in Matlab. The skin friction coefficient, heat transfer coefficient, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…Figure 15 illustrated the smallest eigenvalue σ 1 of both solutions towards ε where σ 1 act as a determinant of the stability solutions. Positive σ 1 implies that the flow is stable whereas negative σ 1 indicates an initial growth of disturbances which resulting that the flow is unstable [55][56][57][58][59][60][61][62][63][64][65]. It is validated from Figure 15 that the first and second solutions have positive and negative σ 1 , respectively which indicates that the first solution is the real solution.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…Figure 15 illustrated the smallest eigenvalue σ 1 of both solutions towards ε where σ 1 act as a determinant of the stability solutions. Positive σ 1 implies that the flow is stable whereas negative σ 1 indicates an initial growth of disturbances which resulting that the flow is unstable [55][56][57][58][59][60][61][62][63][64][65]. It is validated from Figure 15 that the first and second solutions have positive and negative σ 1 , respectively which indicates that the first solution is the real solution.…”
Section: Resultsmentioning
confidence: 88%
“…The execution of the stability analysis is mathematically performed to verify the physical or real solution among all the solutions. There has been much current literature that discussed the importance, formulation and execution of the stability analysis (see Ismail et al [55][56][57], Bakar et al [58,59], Anuar et al [60], Salleh et al [61,62], Najib et al [63], Jamaludin et al [64] and Yahaya et al [65]).…”
Section: Stability Analysismentioning
confidence: 99%
“…This pioneering work offered a proper way to determine the stability of every solution that may exist. Many authors have applied stability analyses in their papers when more than one solution was obtained; some examples can be found in these papers, [31][32][33][34][35][36][37][38][39][40][41], which invariably arrived at the same conclusions on the first and second solutions as Merkin [27].…”
Section: Introductionmentioning
confidence: 99%
“…Rosca and Pop [4], and Weidman et al [10] have shown that the lower branch solutions are unstable (not physically realizable), while the upper branch solutions are stable (physically realizable). Because of the interesting findings mentioned previously, many works on stability analysis have been performed in order to prove the findings which can be found in [28][29][30][31]. Firstly, we consider the eqs.…”
Section: Stability Solutionsmentioning
confidence: 98%